Causes of Abortions Occurring in Red Goats from Maradi, Tessaoua and Madarounfa-Niger - Agnès Tea, Mama; Soromou, Lanan Wassy; Tialla, Dieudonné; Moussa, Fati Mounkaila (Asian Journal of Pharmaceutical Research and Development, 2023)
Abortion, the termination of gestation with expulsion of a non-viable fetus, is a complex process that includes embryonic death and clinical abortion. This subject is of major concern because of its economic and health implications.The aim of this study is to identify the various possible causes of abortion, particularly in the Maradi Red goat. This study used targeted sampling at the Maradi Caprine Centre and in two other departments. From a total of 452 sera analysed by indirect ELISA, 65 (32.5%) were positive for chlamydia, 45 (22.5%) for toxoplasmosis and 0 (0.00%) for brucellosis. To this end, the veterinary and public health services need to reinforce their collaboration in order to establish a programme for controlling the most common zoonoses.